Cutaneous squamous cell carcinoma in patients with chronic lymphocytic leukemia: a systematic review of the literature. (5th August 2021) - Lai, Michela; Pampena, Riccardo; Cornacchia, Luigi; Odorici, Giulia; Piccerillo, Alfredo; Pellacani, Giovanni; Peris, Ketty; Longo, Caterina
Abstract: The continuous improvement of life expectancy of patients with chronic lymphocytic leukemia (CLL) has resulted in increased risk of second primary malignancy that potentially may affect survival and quality of life of CLL patients. We performed a systematic review to assess the risk and the clinical‐pathological features and prognosis of cutaneous squamous cell carcinoma (cSCC) in patients with CLL. We searched PubMed, Embase, and Cochrane Central Register of Control Trials databases for articles published from database inception to December 31, 2019. English‐language studies reporting original data on patients with a specific diagnosis of CLL and cSCC were included. Data were extracted using a standardized extraction form, and any discordance was resolved by consensus. Descriptive data were generated by pooling patients from eligible studies. Of the 4588 non‐duplicate records identified, 55 articles met our inclusion criteria. These studies reported that CLL patients have a 3.2% prevalence of cSCC, with an 11.5% cSCC‐related lethality and an overall risk of metastasis of 5.7% (7.3% for regional lymph node involvement and 3.8% for distant metastasis). The quality of evidence was limited by the high heterogeneity in the design, populations, and objectives of the included studies. This systematic review suggests that cSCC in CLL patients tends to behave less aggressively compared with the solid organ transplant recipients but has a higher morbidity and mortality than in the general population. Future prospective studies are needed to increase the quality of evidence and to determine the best treatment modalities and screening intervals for these patients.